2017
DOI: 10.4172/2155-9597.1000303
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Helminth Parasites of the Lizard, Agama agama in Ile–Ife and Ibadan Southwest Nigeria

Abstract: A parasitological survey was carried out between February and October, 2015 to determine the helminth fauna of the lizard, Agama agama from two locations Ibadan and Ile-Ife, Southwest Nigeria. A total of 133 specimens were collected and examined for helminth infections. The results showed that the overall prevalence of helminth infection in A. agama was 100%. Five species of helminths were recovered comprising three nematodes, Strongyluris brevicaudata (92.5%), Parapharyngodon sp. (89.5%) and unidentified nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…All the helminths recovered from A. picticauda were nematodes, and this fnding corroborates the fndings of other studies that suggest that nematodes form the bulk of the enteric helminths of Agama species [39][40][41][42]. Likewise, Rataj et al [43] found that most of the 18 parasite taxa in specimens of lizards imported into Slovenia were nematodes.…”
Section: Diversity Prevalence and Zoonotic Risk Potential Ofsupporting
confidence: 85%
“…All the helminths recovered from A. picticauda were nematodes, and this fnding corroborates the fndings of other studies that suggest that nematodes form the bulk of the enteric helminths of Agama species [39][40][41][42]. Likewise, Rataj et al [43] found that most of the 18 parasite taxa in specimens of lizards imported into Slovenia were nematodes.…”
Section: Diversity Prevalence and Zoonotic Risk Potential Ofsupporting
confidence: 85%
“…Agama agama was reported to serve as transport and reservoir host to several protozoan and helminth parasites [5]. Parasites from most reptiles can be transferred into a human by carefree attitude.…”
Section: Introductionmentioning
confidence: 99%
“…reproductive period, which may indicate that investment in reproduction is greater than in defense against parasites for both sexes (Zuk & McKean, 1996; Amo et al, 2005; Roberts et al, 2004; Martin et al, 2008; Cabral et al, 2018), as well as behavior and lifestyle of the host species that influence the exposure to parasites (Sowemimo & Oluwafemi, 2017; Ribeiro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%